Late-onset depressive symptoms increase the risk of dementia in small vessel disease. (13th September 2016) - van Uden, Ingeborg W.M.; van der Holst, Helena M.; van Leijsen, Esther M.C.; Tuladhar, Anil M.; van Norden, Anouk G.W.; de Laat, Karlijn F.; Claassen, Jurgen A.H.R.; van Dijk, Ewoud J.; Kessels, Roy P.C.; Richard, Edo; Tendolkar, Indira; de Leeuw, Frank-Erik
Abstract : Objective: We prospectively investigated the role of depressive symptoms (DS) on all-cause dementia in a population with small vessel disease (SVD), considering onset age of DS and cognitive performance. Methods: The RUN DMC study (Radboud University Nijmegen Diffusion Tensor and Magnetic Resonance Cohort) is a prospective cohort study among 503 older adults with SVD on MRI without dementia at baseline (2006), with a follow-up of 5 years (2012). Kaplan-Meier curves stratified for DS and dementia risk were compared using log-rank test. We calculated hazard ratios using Cox regression analyses. Results: Follow-up was available for 496 participants (mean baseline age 65.6 years [SD 8.8]; mean follow-up time 5.2 years). All-cause dementia developed in 41 participants. The 5.5-year dementia risk was higher in those with DS (hazard ratio 2.7, 95% confidence interval 1.4–5.2), independent of confounders. This was driven by those with late-onset DS. Five-year cumulative risk difference for dementia was higher in participants with depressive symptoms who had high baseline cognitive performance (no DS 0.0% vs DS 6.9%, log-rank p < 0.001) compared with those who had low cognitive performance at baseline. Conclusions: Late-onset DS increases dementia risk, independent of SVD. Especially in those with relatively high cognitive performance, DS indicate a higher risk. In contrast to current practice, clinicians should monitor those with DS who also show relatively good cognitive test scores.